19 SUBCUTANEOUS IMPLANTABLE CARDIOVERTER DEFIBRILLATOR AFTER TRANSVENOUS LEAD EXTRACTION: SAFETY, EFFICACY AND OUTCOME. (15th December 2022) - Pittorru, Raimondo; Giacomin, Enrico; Migliore, Federico; Falzone, Pasquale; Bernardo Dall´aglio, Pietro; De Lazzari, Manuel; Vianello, Riccardo; Iliceto, Sabino
Abstract: Background: Subcutaneous implantable cardioverter defibrillator (S-ICD) is a suitable alternative for transvenous ICD (TV-ICD) patients who have undergone transvenous lead extraction (TLE). Limited data are available on the outcome of S-ICD patients implanted after TLE. We assessed the safety, efficacy and outcome of S-ICD implantation after TLE of TV-ICD. Methods: The study population consisted of 36 consecutive patients with a median age of 52 (44-66) years who underwent S-ICD implantation after TLE of TV-ICD. Results and Conclusions: Indications for TLE were: infection (63.4%) and lead malfunction (36.4%). During a median follow-up of 31 months, 3 patients (8.3%) experienced appropriate therapy and 7 patients (19.4%) experienced complications including inappropriate therapy (n=4;11.1%), pulse generator pocket erosion with no evidence of infection (n=2;5.5%) and ineffective therapy (n=1;2.7%).No pocket or systemic device-related infection, lead/hardware dysfunction were reported.Premature device explantation occurred in 4 patients (11%). Eight patients (22.2%) died during follow-up, six of them (75%) because of refractory heart failure (HF).There were no S-ICD-related deaths. Predictors of mortality included NYHA class ≥2 (HR 5.05;95% CI 1.00–26.38;p=0.04), hypertension (HR 22.72;95% CI 1.05–26.31;p=0.02), diabetes (HR 10.64;95% CI 2.05-55.60; p=0.001) and ischemic heart disease (HR 5.92;95% CI 1.17–30.30;p= 0.01). Our study provides evidences on the use of S-ICD as an ideal alternative after TV-ICD explantation for both infection and lead failure. Mortality of S-ICD patients who underwent TV-ICD explantation does not appear to be correlated with the presence of a prior infection, S-ICD therapy (appropriate or inappropriate), or S-ICD complications but rather to worsening of HF or other comorbidity.